Anion Recognition and Cation-Induced Molecular Motion in a Heteroditopic [2]Rotaxane. - Leontiev, A; Jemmett, C; Beer, P (2010)
A heteroditopic [2]rotaxane consisting of a calix[4]diquinone-isophthalamide macrocycle and 3,5-bis-amide pyridinium axle components with the capability of switching between two positional isomers in response to barium cation recognition is synthesised. The anion binding properties of the rotaxane's interlocked cavity together with Na(+), K(+), NH(4) (+) and Ba(2+) cation recognition capabilities are elucidated by (1)H NMR and UV-visible spectroscopic titration experiments. Upon binding of Ba(2+), molecular displacement of the axle's positively charged pyridinium group from the rotaxane's macrocyclic cavity occurs, whereas the monovalent cations Na(+), K(+) and NH(4) (+) are bound without causing significant co-conformational change. The barium cation induced shuttling motion can be reversed on addition of tetrabutylammonium sulfate.